A Mediation Analysis of Work Engagement in the Relationship between Transformational Leadership, Organizational Culture, and OCB - Irvan Wijaya; Sih Darmi Astuti; Dwi Eko Waluyo; Amalia Nur Chasanah (Fakultas Ekonomi dan Bisnis Universitas Dian Nuswantoro, 2025)
Human resources are the most important and determining assets in an organization. Human resources who are competent, highly motivated and able to work well are the resources needed by the company. Organizational citizenship behavior (OCB) is a concrete form of an employee in every company or organization to lighten the workload of other colleagues, without forgetting the main work that must be done by that individual. Many factors influence OCB, including work engagement, leadership and organizational culture. This research aims to examine the influence of Work Engagement, Leadership and Organizational Culture variables on OCB in PT Fajarmas Murni employees. The population used in this research were all employees of PT Fajarmas Murni who had worked for at least 2 years. The sample in this study was 164 respondents. Data was collected using a survey method using a questionnaire. This research uses Structural Equation Modeling (SEM) data analysis techniques which are operated using the SmartPLS 3 program. The results of the research show that Organizational Culture and Work Engagement have a significant effect on OCB, while transformational leadership has no significant effect and Transformational Leadership has a significant effect on Work Engagement while Organizational Culture does not have a significant effect on work engagement.